Omnichannel Based Integrated Marketing Communication At Tripatria Innovation Marketing Program - Aliya Khoirunnisa; Endy Gunanto Marsasi (UNIVED Press, 2024)
This study explores the application of an Integrated Marketing Communication (IMC)-based omnichannel approach in Tripatria's Innovation Marketing Program. This program aimed to increase brand awareness and consumer trust through an integrated online marketing strategy. The program, conducted over six months, successfully engaged general consumers and healthcare professionals, leading to increased interactions on social media and product purchases. The findings highlight the significant impact of a well-executed omnichannel strategy on consumer behavior and brand perception and emphasize the need for continuous innovation and adaptation in marketing strategies to remain competitive in the dynamic healthcare market. Future research should investigate the long-term effects of such marketing programs on customer loyalty and retention.